Defying Silence: Immigrant Women Workers, Wage Theft, and Anti-Retaliation Policy in the States - Taykhman, Nicole (Columbia Journal of Gender and Law, 2016)
A recent New York Times exposé highlighted the inner workings of the nail salon industry in New York City, and revealed to the public how rampant wage theft props up an industry that relies on low-wage, undocumented women workers. New York’s response provides a starting point to consider how governments should respond to wage theft as it affects undocumented women. There are various legal regimes available for responding to wage theft, but each presents serious shortcomings when it intersects with the immigration system, primarily because of the threat of retaliation. As federal protections are weak or exacerbate the victimization of undocumented women, states should strengthen anti-retaliation protections specific to undocumented workers. California passed legislation in this area which New York should adopt. While the protections provided in California’s legislation would strengthen each of the various legal regimes discussed, they would also empower undocumented women to break the silence imposed by retaliation and tell narratives that resist victimization.